블랙 렌틸콩 추출물 첨가 약과의 품질 특성 - 오지연(Ji-Yeon Oh ); 심기현(Ki Hyeon Sim) (東아시아食生活學會誌, 2017)
This study added black lentil ethanol extract to Yakgwa at ratios of 0%, 0.5%, 1.0%, and 2.0%, and its quality characteristics were compared to those of the synthetic antioxidant BHT added to Yakgwa. Yakgwa with black lentil extract had lower moisture content than Yakgwa with BHT (3.98%) but higher content than the control group (5.72%). Higher black lentil extract resulted in less moisture content (p<0.001) as well as a faster expansion rate and oil absorption rate (p<0.001). Scanning Electron Microscopy (SEM) showed that as black lentil extract content increased, pores merged and collapsed, whereas the number of pores decreased and pore size became larger. For chromaticity, all L, a, and b values of the group containing black lentil extract were higher compared to the control group and group with BHT (p<0.001). For texture, as amount of added black lentil extract increased, hardness (p<0.001) and gumminess (p<0.01) increased while cohesiveness (p<0.01) decreased compared to the control group. For sensory characteristics, Yakgwa with 1.0% black lentil extract showed the best preference for all items except for off-flavor. Thus, 1.0% black lentil added to Yakgwa was the best in terms of functionality including preference.